Prosthetic shoulder arthroplasty in patients 40 years or younger: outcomes stratified by diagnosis and surgery - Samer S. Hasan; Leslie E. Schwindel; Cassie M. Fleckenstein (Clinics in Shoulder and Elbow, 2022)
Background The outcomes of patients 50–55 years old or younger undergoing prosthetic shoulder arthroplasty (PSA) may not generalize to younger patients. We report outcomes following PSA in a consecutive series of patients 40 years or younger. We hypothesize that total shoulder arthroplasty (TSA) provides better outcome and durability than resurfacing hemiarthroplasty (RHA). Methods Patients were stratified by diagnosis and surgical procedure performed, RHA or TSA. Active range of motion and self-assessed outcome were evaluated preoperatively and at final follow-up. Results Twenty-nine consecutive PSAs were identified in 26 patients, comprising 9 TSAs and 20 RHAs, with a minimum of 2-year follow-up. Twelve PSAs were performed for chondrolysis. Mean active forward elevation, abduction, external rotation, and internal rotation improved significantly (p<0.001 for all). Mean pain score improved from 6.3 to 2.1, Simple Shoulder Test from 4.0 to 9.0, and American Shoulder and Elbow Surgeons score from 38 to 75 (p<0.001 for all). Patients undergoing RHA and TSA had similar outcomes; but three RHAs required revision, two of these within 4 years of implantation. Four of five patients undergoing revision during the study period had an original diagnosis of chondrolysis. Conclusions PSA in young patients provides substantial improvement in active range of motion and patient reported outcomes irrespective of diagnosis and glenoid management. However, patients undergoing RHA, especially for chondrolysis, frequently require subsequent revision surgery, so that RHA should be considered with caution in young patients and only after shared decision-making and counsel on the risk of early revision to TSA.